Memes de internet como reforzadores de identidades políticas: estudio de caso de la crisis sociopolítica boliviana de 2019 - Ewel, Nicolás (2020)
This research paper describes the effects that memes had during a period of the political crisis in Bolivia during October/November 2019. To this end, a compilation of political memes was made, understanding these as a socio-cultural artifact belonging to the Internet. These were subsequently unraveled in two focus groups. Through these, it was evidenced that memes produced and consumed at this time reinforced pre-existing political identities. Furthermore, we suggest that there are quality standards under which they are classified by users.